THE IMPROVEMENT OF EXPERIMENTAL SKILLS BY IMPLEMENTING PREDICT, OBSERVE, EXPLAIN (POE) LEARNING MODEL IN LEARNING SCIENCE - Linda Pradina Candra; Peduk Rintayati; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2018)
The objective of this research is to improve the experimental skills of 4th grade students of SD N Surakarta year 2017/2018 through the application of Predict, Observe, Explain (POE) learning model in learning natural science. This research is a classroom action research conducted in three cycles and each cycle consists of two meetings. The subjects of this research are teacher and fourth graders of SDN N Surakarta Year 2017/2018 consisting of 12 students. Data collection techniques used are observation, interview, and documentation. Data analysis technique used is inte-ractive analysis model which has four components consisting of data collecting, data reduction, data display, and conclusion. Data validity test uses content validity and triangulation. Based on the results of research, it can be concluded that the application of Predict, Observe, Explain (POE) learning model can improve the experimental skills of 4th grade students of SD N Surakarta Year 2017/2018.